2012
DOI: 10.3136/fstr.18.667
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Collagen Hydrolysate-derived Peptides Inhibit Tumor Necrosis Factor-α-induced Inflammatory Response in Endothelial Cells

Abstract: Novel peptides derived from chicken collagen hydrolysate (CCH) were confirmed to have a vasoprotective effect after ingestion and absorption to vessels; however, their endovascular mechanism of action required clarification. Therefore, using human umbilical vein endothelial cells (HUVECs), in which inflammation had been induced by tumor necrosis factor-α (TNF-α), we investigated the mechanism by which CCH-derived peptides inhibited the vascular inflammatory response. Expression of soluble intercellular adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Hydrolysates of collagen and gelatin have also been reported to have potential anti‐inflammatory activity (Hartog, Cozijnsen, DE Vrij, & Garssen, ; Kouguchi et al, ; Ramadass et al, ; Sae‐leaw et al, ). Indeed, Sae‐leaw et al () reported that the Alcalase hydrolysis of seabass skin gelatin produced hydrolysates with anti‐inflammatory activity in RAW264.7 cells, decreasing levels of the pro‐inflammatory cytokines interleukin (IL)‐6 and IL‐1β.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolysates of collagen and gelatin have also been reported to have potential anti‐inflammatory activity (Hartog, Cozijnsen, DE Vrij, & Garssen, ; Kouguchi et al, ; Ramadass et al, ; Sae‐leaw et al, ). Indeed, Sae‐leaw et al () reported that the Alcalase hydrolysis of seabass skin gelatin produced hydrolysates with anti‐inflammatory activity in RAW264.7 cells, decreasing levels of the pro‐inflammatory cytokines interleukin (IL)‐6 and IL‐1β.…”
Section: Introductionmentioning
confidence: 99%
“…A commercial collagen hydrolysate (Colnatur) has been reported to inhibit zymosan‐induced inflammation in mice and decreased the production of IL‐6 in whole blood cells (Hartog et al, ). Collagen, from chicken feet hydrolyzed using a fungal protease, produced peptides that inhibited tumor necrosis factor (TNF)‐α induced inflammation in human endothelial cells in culture (Kouguchi et al, ). In addition, a hydrolysate generated from the tryptic digestion of rat‐tail tendon collagen was reported to have anti‐inflammatory activity in vivo, reducing rectal bleeding and downregulating IL‐6, IL‐1β, and TNF‐α expression in colon tissues in dextran sodium sulfate‐induced colitis in mice (Ramadass et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…12) Pro-Hyp has been reported to promote synthesis of hyaluronic acid 13) and formation of articular cartilage, 14) and Pro-Hyp and Hyp-Gly inhibit tumor necrosis factor induced inflammatory response. 15) Gly-Pro reduces the blood pressure. 16) Various beneficial effects observed after ingestion of collagen hydrolysate are considered to be closely related to these metabolized peptides.…”
mentioning
confidence: 99%
“…2) In our previous study, these peptides reduced the expression of such inflammation markers as ICAM-1, VCAM-1, IL-8, and inducible nitric oxide synthase (iNOS) which were up-regulated by TNF-. 24) These results suggest that the modulatory effects of CCH on the circulation system, for example the improvement of arterial flexibility, might be due to the inhibition of endothelial inflammation.…”
Section: Discussionmentioning
confidence: 95%